Sea Star Diversity and their Epibionts in Taklong Island - Lacson, Lorie Mie G. (2015.)
Sea stars are organisms that play an important role in coastal ecosystems such as seagrass beds and reefs. Their feeding behaviour affects energy flow in these ecosystems. They also serve as settling areas or substrates for small organisms, which add to the biodiversity at sea where there is stiff competition for space. Six (6) species of sea stars were encountered in Taklong Island National Marine Reserve , Guimaras, namely Protoreaster nodosus, Linckia laevigata, Archaster typicus, Culcita novaeguineae, Archanthaster planci, and Nardoa tuberculata c.f. Two of the species, namely A. planci and N. tuberculata c.f. were also observed but were outside of the plots established. Sampling yielded a total of 177 individuals in 4 species. The most numerous and most frequently encountered species was P. nododus(n=142). By taking note of the substrates wherein individuals were found, it may be said that sea stars were found in habitats wherein their preferred food is abundant. Sea star species diversity and species richness was low in all sites. A total of 497 epibionts from 56 operational taxonomic units (UTOs) were observed on the surfaces of sea star hosts. P. nodosus had the highest epiboint species diversity. A. typicus was the most fouled sea star, having the highest number of epibionts. Copepods and foraminiferans were the most abundant and frequently encountered epibionts. Other ectocommenals and ectoparasites were observed. Overall, there was a very high diversity of epibionts present on the surfaces of the sea stars of Taklong Island.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Sea Star; Sea Star -- Epibionts -- Taklong Island